2020
DOI: 10.1002/nau.24304
|View full text |Cite
|
Sign up to set email alerts
|

Brain activation patterns of female multiple sclerosis patients with voiding dysfunction

Abstract: Aims We compared brain activation patterns between female multiple sclerosis (MS) patients with voiding dysfunction (VD) and those without. We aim to expand current knowledge of supraspinal correlates of voiding initiation within a cohort of female MS patients with and without VD. Materials and Methods Twenty‐eight ambulatory female MS patients with stable disease and lower urinary tract dysfunction were recruited for this study. Subjects were divided into group 1, without VD (n = 14), and group 2, with VD (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 30 publications
2
3
0
Order By: Relevance
“…Our research team has extensively examined how the brain controls LUT functions in women with MS [ 30 40 ]. We have also observed similar results indicating elevated BOLD signals in these specific ROIs within circuit 2 when individuals with MS and NOAB experience a strong urge to void, suggesting an abnormal perception of bladder volume in these individuals [ 32 , 35 ]. Although the precise mechanisms governing the interactions among these circuits are not yet understood, it is now apparent that they do not operate independently in either healthy individuals or those with OAB/NOAB [ 29 ].…”
Section: Introductionsupporting
confidence: 68%
“…Our research team has extensively examined how the brain controls LUT functions in women with MS [ 30 40 ]. We have also observed similar results indicating elevated BOLD signals in these specific ROIs within circuit 2 when individuals with MS and NOAB experience a strong urge to void, suggesting an abnormal perception of bladder volume in these individuals [ 32 , 35 ]. Although the precise mechanisms governing the interactions among these circuits are not yet understood, it is now apparent that they do not operate independently in either healthy individuals or those with OAB/NOAB [ 29 ].…”
Section: Introductionsupporting
confidence: 68%
“…Clinical data have suggested that cortical dysfunction may contribute to MS bladder dysfunction (Khavari et al, 2020). In this study, we show for the first time that cortical demyelination in a standard MS mouse model (Ramasamy & Smith, 2021a, 2021b can produce an MS bladder dysfunction phenotype.…”
Section: Discussionsupporting
confidence: 49%
“…However, neither the standard clinical diagnoses nor a spinal‐centric MS bladder disease model is fully consistent with clinical physiologic findings (Leitner et al, 2016; Rantell et al, 2018), nor have yielded routinely safe and effective therapies for patients (Phé et al, 2016). Clinical data have suggested that cortical dysfunction may contribute to MS bladder dysfunction (Khavari et al, 2020). In this study, we show for the first time that cortical demyelination in a standard MS mouse model (Ramasamy & Smith, 2021a, 2021b) can produce an MS bladder dysfunction phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…[9,10] Dynamic imaging studies, such as positron emission tomography-computed tomography (PET-CT) and functional magnetic resonance imaging (fMRI) modalities, have been implemented to better characterize this complex disease process. [11][12][13] Previously, our team found distinct functional connectivity (FC) patterns using fMRI [13] with more damage in the left anterior thalamic radiation (ATR) on diffusion tensor imaging (DTI) [14] in patients with VD compared to those without. In this study, we aim to assess the grey and white matter of female MS patients with DSD, specifically the FC of brain regions that are activated at the initiation of voiding, and the integrity of two white matter tracts; the ATR and the superior longitudinal fasciculus (SLF), via their fractional anisotropy (FA) and mean diffusivity (MD) values.…”
Section: Introductionmentioning
confidence: 99%